2004
DOI: 10.1213/01.ane.0000138034.73465.d3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Hydrothorax in the Absence of Ascites: Respiratory Failure in a Cirrhotic Patient

Abstract: The frequency of hepatic hydrothorax in cirrhotic patients is reported to be approximately 5%. The pleural effusion is predominantly right-sided (85% of cases) but may be bilateral. Although most often accompanied by significant ascites, it can occur in its absence. We report a case of a right-sided acute hepatic hydrothorax as a result of residual motor blockade during anesthesia recovery and without previous evidence of clinical ascites. This complication should be considered by the anesthesiologist in every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…13,17 Pleural effusion may occur without any accumulation of fluid in the peritoneal cavity when the rate of ascites formation is equal to the rate of pleural reabsorption. 18 Previous studies have reported that the prevalence of pleural effusion in patients with endstage liver disease ranged from 5% to 10%. 19,20 Pleural effusion was found in 16.3% of our study patients, which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…13,17 Pleural effusion may occur without any accumulation of fluid in the peritoneal cavity when the rate of ascites formation is equal to the rate of pleural reabsorption. 18 Previous studies have reported that the prevalence of pleural effusion in patients with endstage liver disease ranged from 5% to 10%. 19,20 Pleural effusion was found in 16.3% of our study patients, which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Here again, the proposed mechanism is the shift of fluid from the peritoneal cavity to the pleural space. [37] The negative intrathoracic pressure in conjunction with diaphragmatic openings permits the passage of fluid as soon as ascites occurs. It is thought that in these cases the reabsorption capacity of the pleura is equal to the production of ascites; so that ascites accumulation will not occur.…”
Section: Hepatic Hydrothoraxmentioning
confidence: 99%
“…It is typically a right-sided process (85%) [59]. Interestingly, cases of hepatic hydrothorax in the absence of ascites have been well described in the literature [60]. The likely reason behind this is that negative intrathoracic pressure on inspiration moves peritoneal fluid preferentially toward the chest.…”
Section: Pathogenesismentioning
confidence: 99%